First-in-human assessment of safety and immunogenicity of low and high doses of Plasmodium falciparum malaria protein 013 (FMP013) administered intramuscularly with ALFQ adjuvant in healthy malaria-naïve adults. Issue 40 (22nd September 2022) - Hutter, Jack N; Robben, Paul M.; Lee, Christine; Hamer, Melinda; Moon, James E.; Merino, Kristen; Zhu, Lei; Galli, Heather; Quinn, Xiaofei; Brown, Dallas R.; Duncan, Elizabeth; Bolton, Jessica; et al.
Highlights: This is the first-in-human trial of both FMP013 and the ALFQ adjuvant. The vaccine evinced significant humoral and cell mediated immunogenicity. The vaccine demonstrated an acceptable safety profile. The results of this trial have led to an efficacy trial using CHMI. Abstract: The global burden of malaria remains substantial. Circumsporozoite protein (CSP) has been demonstrated to be an effective target antigen, however, improvements that offer more efficacious and more durable protection are still needed. In support of research and development of next-generation malaria vaccines, Walter Reed Army Institute of Research (WRAIR) has developed a CSP-based antigen (FMP013) and a novel adjuvant ALFQ (Army Liposome Formulation containing QS-21). We present a single center, open-label, dose-escalation Phase 1 clinical trial to evaluate the safety and immunogenicity of the FMP013/ALFQ malaria vaccine candidate. In this first-in-human evaluation of both the antigen and adjuvant, we enrolled ten subjects; five received 20 μg FMP013 / 0.5 mL ALFQ (Low dose group), and five received 40 μg FMP013 / 1.0 mL ALFQ (High dose group) on study days 1, 29, and 57. Adverse events and immune responses were assessed during the study period. The clinical safety profile was acceptable and there were no serious adverse events. Both groups exhibited robust humoral and cellular immunological responses, and compared favorably with historical responses reported for RTS, S/AS01. Based on a lower reactogenicity profile, the 20 μg FMP013 / 0.5 mL ALFQ (Low dose) was selected for follow-on efficacy testing by controlled human malaria infection (CHMI) with a separate cohort. Trial Registration: Clinicaltrials.gov Identifier NCT04268420 (Registered February 13, 2020)